Harpacticoida (Copepoda) in the plankton of Ushuaia and Golondrina Bays, Beagle Channel, Argentina - Biancalana, Florencia (2020)
Harpacticoid copepods form a diverse and abundant group of the meiofauna in marine benthic habitats. Moreover, harpacticoids are frequently found in planktonic samples particularly in shallow and algae-covered coastal waters. Despite their high abundance, little is known about their taxonomy and importance as a component of the food web in the Southern bays of Argentina. Mesozooplankton samples and environmental data were obtained seasonally from Ushuaia and Golondrina Bays (August 2004 to June 2005) and analyzed for the composition and abundance of harpacticoid copepods. Remarkable seasonal changes in the harpacticoid communities were observed. In Ushuaia Bay, nitrogenated nutrients, chlorophyll a, salinity, and temperature were the prevailing environmental parameters that influenced the harpacticoid community, giving rise to different harpacticoid assemblages. The results highlight the importance of the community of Harpacticoida in both bays and provide background data for further studies on zooplankton communities and monitoring programs in marine systems.